2001
DOI: 10.1515/znc-2001-1-224
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Chemical Study of Maytenus ilicifolia Mart. Reiss and Maytenus robusta Reiss (Celastraceae)

Abstract: This work describes a comparative qualitative and quantitative chemical analysis of Maytenus ilicifolia and Maytenus robusta (Celastraceae), extracts by high-resolution gas chromatography (HRGC), using external standards as the method of determination and thin layer chromatographic (TLC). The results show that both plants have a similar chromatographic profile. However, M. robusta exhibited about three times higher concen tration of triterpene friedelin than M. ilicifolia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 0 publications
1
16
0
2
Order By: Relevance
“…Studies performed with M. ilicifolia leaves extracts pointed its anti ulcerogenic (Carlini and Braz, 1998;Souza-Formigoni and Oliveira, 1991;Niero et al, 2001), analgesic , antitumoral (Fox, 1991), and abortive (Montanari and Bevilacqua, 2002) properties.…”
Section: Introductionmentioning
confidence: 99%
“…Studies performed with M. ilicifolia leaves extracts pointed its anti ulcerogenic (Carlini and Braz, 1998;Souza-Formigoni and Oliveira, 1991;Niero et al, 2001), analgesic , antitumoral (Fox, 1991), and abortive (Montanari and Bevilacqua, 2002) properties.…”
Section: Introductionmentioning
confidence: 99%
“…As propriedades antiulcerogênicas dessa espécie têm sido atribuídas aos triterpenos (Vilegas et al, 1994;Niero, 2001) e fl avonóides (Vilegas et al, 1999;Leite et al, 2001). No entanto, Queiroga et al (2000), avaliando…”
Section: Introductionunclassified
“…The material obtained was filtered and concentrated by evaporation and negative pressure. A preliminary investigation of the composition of the extracts were performed using spectroscopy methods such as infrared, 1 H and 13 C nuclear magnetic resonance, and bidimensional techniques (Krogh et al, 1999;Niero et al, 1999;Silva et al, 2000;Niero et al, 2001;Souza, 2006;Buskühl, 2007). The methanol extracts obtained were kept in the dark in desiccators, together with silica to remove the moisture.…”
Section: Plant Materials Collectionmentioning
confidence: 99%
“…Studies of phytochemical and biological activity have identified several compounds present in these plants, showing several activities such as antinociceptive activity against C. brasiliense (Silva et al, 2001;Isaias, et al, 2004;, I. pes-caprae (Krogh et al, 1999;Souza et al, 2000), M. eleagnoides (Souza et al, 2007), M. robusta (Niero et al, 2001) and R. imperialis (Niero et al, 1999;Niero et al, 2002;Ardenghi et al, 2006), and also molluscicicidal activity against C. brasiliense (Gasparotto Jr. et al, 2005) and cytotoxic activity against V. scorpioides (Buskühl, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation